Planning for the unexpected: Exploring the 2024 Global IT Outage (GITO) impact on critical infrastructures - Jaime Santos-Reyes (Sustainable Futures)
The paper presents the results of an analysis of the 2024 Global IT Outage (GITO) disruptive event that occurred on 19 July 2024, causing worldwide disruptions to air travel, health, systems, among others. The UK critical infrastructure systems (CIs) have been used as a case study in the present analysis. The employed approach has been the use of a systemic safety management system (SSMS) model. Some key findings: a) Transport (Air travel) and health CIs were fragile to the event, b). Energy, water, and food CIs exhibited robustness. The energy sector's robustness has to do with its inhouse-software system and its no dependency on the CrowdStrike's software; water and food seem not to be having a strong dependence on the software; however, it is unclear whether this could have been maintained had the emergency lasted for more days or months, c). The GITO disruption effects varied within the CI system, e.g., transport, and financing sectors. Some key conclusions: a). Robustness to disruptive events such as the present case study requires CIs in-house technologies or back-up systems; b). Due to interdependencies, a robust subsystem within a CI system is not enough to withstand a disruptive event, i.e., it still will be fragile; c). Decision-makers should plan for unexpected events; d). The employed model has the potential to modelling interdependence among CIs. More research is needed on the analysis of events such as the presented here-in to learn from these and further enhance the existing knowledge on disruptive events on CIs.